Respiratory pathogens adopt a chronic lifestyle in response to bile. - F Jerry Reen (Public Library of Science (PLoS), 2012)
Chronic respiratory infections are a major cause of morbidity and mortality, most particularly in Cystic Fibrosis (CF) patients. The recent finding that gastro-esophageal reflux (GER) frequently occurs in CF patients led us to investigate the impact of bile on the behaviour of Pseudomonas aeruginosa and other CF-associated respiratory pathogens. Bile increased biofilm formation, Type Six Secretion, and quorum sensing in P. aeruginosa, all of which are associated with the switch from acute to persistent infection. Furthermore, bile negatively influenced Type Three Secretion and swarming motility in P. aeruginosa, phenotypes associated with acute infection. Bile also modulated biofilm formation in a range of other CF-associated respiratory pathogens, including Burkholderia cepacia and Staphylococcus aureus. Therefore, our results suggest that GER-derived bile may be a host determinant contributing to chronic respiratory infection.